Menanamkan Literasi dan Numerasi Sejak Dini melalui Etnomatematika: Suatu Desain Model Pembelajaran Berbasis Budaya - Khasanah, Ismatul; Pusari, Ratna Wahyu; Rakhmawati, intan; Putriyanti, Lina (Malih Peddas (Majalah Ilmiah Pendidikan Dasar), 2025)
This research was all about finding a fun and effective new way to help young kids understand literacy and numeracy. We used an ethnomathematics approach, which means we taught math by connecting it to local culture. The study took place on February-June 2025, at TK Nusa Indah in Semarang, where we observed one class of preschool children. We gathered our data by watching them, talking to their teacher, and looking at the things they made.The results were great! The mask-making activity was a huge success. A full 90% of the kids were able to understand and explain geometric shapes (like circles and triangles) and numbers (for example, counting the eyes on their masks) in a creative way. This showed us that when learning is tied to things that are familiar and interesting to them—like their own local culture—abstract ideas become much easier to grasp and feel more meaningful. This approach proves that education can be a bridge between a child’s culture and their cognitive development.